PERENCANAAN PERLUASAN APRON C (DOMESTIK DAN INTERNASIONAL) DENGAN PERKERASAN RIGID DI BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Elga Apriadha Dwinata; Sukamto; Luky Surachman (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
The high movement of aircraft at the International Airport I Gusti Ngurah Rai Bali, Is not yet balanced with the air equipped with adequate especially in the apron caused mobilization did not go well. It underlies the need of expansion apron north to fulfill plane capacity to operate. This needs to be planned expansion of an apron north by using the method of FAA (manual and software) and method of forecasting. According to analysis and the results then the planned expansion of the apron dimension is 64.677,72 m² for the addition of 4 parking stands by increasing specification of aircraft operating into aircraft 4E and 4C category. A thick slab of concrete that is obtained will be used of 52.07 cm concrete quality K-400, 25.4 cm subbase thickness and subgrade CBR amounted to 6%